Dukungan Orang Tua dengan Interaksi Sosial pada Anak Retardasi Mental : Parental Support with Social Interaction in Mentally Retarded Children - Maura Fachriza Asral; Fiki Wijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Parental support is important for the child's development process. Children with mental retardation really need parental support in terms of emotional support, instrumental, appreciation and informational support in helping children with mental retardation to interact socially with their environment. This study aims to determine the relationship between parental support and social interaction in mentally retarded children at SLB N Ungaran. This study used quantitative methods with a correlative research design using a crossectional approach. Samples were taken with total sampling technique with a total of 44 respondents. Data analysis in this study used kendall's tau b test. The results of research on 44 respondents Parental support obtained by 38 respondents (86.4%) good support and good social interaction with 36 respondents (81.8%) with p value (0.001) <0.05. This study has a correlation coefficient value of 0.509 which means that this study has a moderate relationship and leads to a positive relationship. Parental support obtained by 38 respondents (86.4%) good support and good social interaction with 36 respondents (81.8%). There is a relationship between parental support and social interaction of children with mental retardation in SLB N Ungaran. With this research, it is hoped that good parental support can be maintained or improved so that the social interaction of children with mental retardation is getting better ABSTRAK Dukungan Orang tua penting bagi proses perkembangan anak. Anak dengan retardasi mental sangat membutuhkan dukungan orang tua dari segi dukungan emosional, instrumental, penghargaan dan dukungan informasional dalam membantu anak dengan retardasi mental untuk berinteraksi sosial dengan lingkungannya. Penelitian ini bertujuan untuk mengetahui hubungan dukungan orang tua dengan interaksi sosial pada anak retardasi mental di SLB N Ungaran. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian korelatif menggunakan pendekatan crossectional. Sampel diambil dengan tehnik total sampling dengan total 44 responden. Analisis data pada penelitian ini menggunakan uji kendall’s tau b. Hasil penelitian pada 44 responden didapatkan dukungan orang tua sebesar 38 responden (86,4%) dukungan baik dan interaksi sosial baik dengan 36 responden (81,8%) dengan p value (0,001) < 0,05. Penelitian ini memiliki nilai koefisien korelasi sebesar 0,509 yang memiliki makna bahwa penelitian ini memiliki hubungan cukup dan mengarah pada hubungan positif. Ada hubungan antara dukungan orang tua dengan interaksi sosial anak dengan retardasi mental di SLB N Ungaran. Dengan adanya penelitian ini diharapkan dukungan orang tua yang baik mampu dipertahankan atau ditingkatkan agar interaksi sosial anak dengan retardasi mental semakin baik